2021
DOI: 10.1101/2021.03.21.21254050
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emotional responses toward COVID-19: A longitudinal assessment of age differences

Abstract: The current study investigates the relation between age and emotional responses and coping strategies at two moments during the spread of COVID-19 in Poland, namely the first peak (March-May 2020) and the second pick (October-December 2020). A sample of 414 individuals between the ages of 18 and 81 were asked to rate the intensity of the shock, sadness, anger, and fear they experienced due to COVID-19 and respond to items from the Brief Cope questionnaire. The present findings demonstrate that anger was consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
1
0
3
Order By: Relevance
“…This definition agrees with the claim of stress theories that the major function of coping is to reduce fear and anxiety, raised by a stressful condition, and restore adjustment ( Breznitz, 1983 ; Lazarus, 1983 ). Research has shown that individuals who have used more often emotion-focused coping in the first phase of the COVID-19 pandemic were likely to experience less anger and sadness throughout this pandemic ( Malesza, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This definition agrees with the claim of stress theories that the major function of coping is to reduce fear and anxiety, raised by a stressful condition, and restore adjustment ( Breznitz, 1983 ; Lazarus, 1983 ). Research has shown that individuals who have used more often emotion-focused coping in the first phase of the COVID-19 pandemic were likely to experience less anger and sadness throughout this pandemic ( Malesza, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Najczęściej zaobserwowane w badaniach reakcje emocjonalne wywołane pandemią koronawirusa to: strach, lęk, niepokój, zmartwienie oraz niepewność (Gambin i in., 2021;Lee, 2020;Li, Luan, Li, Hertwig, 2021;Parlapani i in., 2020;Trnka, Lorencova, 2020). Badanie przeprowadzone w Polsce w momencie dwóch szczytów zachorowań (maj oraz październik 2020) pokazało dominację i utrzymywanie się dwóch głównych emocji: szoku oraz strachu (Malesza, 2021). Ponieważ pandemia COVID-19 nie jest pojedynczym wydarzeniem, ale stanem rozciągniętym w czasie -emocje, które wywołuje, również ulegają zmianom.…”
Section: Reakcje Emocjonalne Na Pandemię Koronawirusaunclassified
“…Aby uchwycić skomplikowany obraz zmieniających się pod wpływem pandemii emocji, konieczne są badania podłużne, jednak większość z przeprowadzonych w kontekście pandemii COVID-19 badań to dwu-lub trzyfalowe badania (m.in. Gutiérrez-Cobo i in., 2021;Li i in., 2021;Malesza, 2021;van der Velden i in., 2021;Wang i in., 2020), co daje tylko wycinkowy obraz rzeczywistości. Ponadto nieliczne badania jakościowe dotyczące reakcji na pandemię (np.…”
Section: Badanie Własneunclassified
See 1 more Smart Citation